Social Media Hate Crime and American Judicial Rhetoric: A Study - Nehaluddin AHMAD; Gary LILIENTHAL; Zaki ZAINI (Communications of International Proceedings, 2022)
The article’s doctrinal research methodology examines the available multi-jurisdictional evidence of hate and bias crime. It then synthesizes an outcome to explain its elaboration into social media hate crime in the context of American law. The argument begins with a reader’s special briefing on the rhetorical theory of judicial construct elaboration. Then, the discussion moves to a contextual analysis of the American judicial rhetoric in developing hate crime laws. The argument then explains motive, purpose, and intention as relevant to hate crime. Before the article’s conclusion, the statement sets out an explanation of operative hate crime statutes and the case law in the US.
Keywords: hate crime; bias crime; motive; criminal penalties; social media; hostility